Molecular and genetic characterization of the allelic variants of Du215, Du281, Du323, and Du47G microsatellite loci in parthenogenetic lizard Darevskia armeniaca (Lacertidae) - Girnyk, A. E.; Vergun, A. A.; Omelchenko, A. V.; Petrosyan, V. G.; Korchagin, V. I.; Ryskov, A. P. (Russian journal of genetics, 2017)
A key issue in the study of unisexual (parthenogenetic) vertebrate species is the determination of their genetic and clonal diversity. In pursuing this aim, various markers of nuclear and mitochondrial genomes can be used. The most effective genetic markers include microsatellite DNA, characterized by high variability. The development and characterization of such markers is a necessary step in the genetic studies of parthenogenetic species. In the present study, using locus-specific PCR, for the first time, an analysis of allelic polymorphism of four microsatellite loci is performed in the populations of parthenogenetic species Darevskia armeniaca . In the studied populations, allelic variants of each locus are identified, and the nucleotide sequences of each allele are determined. It is demonstrated that allele differences are associated with the variation in the structure of microsatellite clusters and single nucleotide substitutions at fixed distances in flanking DNA regions. Structural allele variations form haplotype markers that are specific to each allele and are inherited from their parental bisexual species. It is established which of the parental alleles of each locus were inherited by the parthenogenetic species. The characteristics of the distribution and frequency of the alleles of microsatellite loci in the populations of D. armeniaca determining specific features of each population are obtained. The observed heterozygosity of the populations at the studied loci and the mutation rates in genome regions, as well as Nei’s genetic distances between the studied populations, are determined, and the phylogenetic relationships between them are established.